Evolution, Revolution, and Technology Scaling—The Impact on ESD and EOS Reliability - Voldman, Steven H. (Frontiers in Materials, 2018)
In the scaling of semiconductor devices, evolutionary and revolutionary modifications are made in the device dimension, structural changes and dimensions. The effect of MOSFET scaling on electrostatic discharge (ESD) and electrical overstress (EOS) reliability and robustness have both positive and negative implications. In this publication, the evolutionary and revolutionary technology changes on how they influence the ESD and EOS results will be discussed in full detail. The paper will discuss changes in the substrate, wells, isolation, source/drain regions, gate dielectrics, inter-level dielectrics and interconnects.